Mechanism of Roof Shock in Longwall Coal Mining under Surface Gully. (21st May 2015) - Fan, Gangwei; Zhang, Dongsheng; Wang, Xufeng
Abstract : The paper presents an interpretation on the abnormal roof shock in longwall coal mining under gullies using physical modeling, numerical modeling, and mechanical analysis. The modeling results show that the roof movement causes the shock load onto the stope in longwall coal mining under surface gully. The triggering mechanism of shock load depends on the direction of the face retreat with respect to the bottom of the surface gully. The slope tends to slide along the interface plane with a long periodical weighting intervals when mining towards the bottom of the gully (downslope direction), while the overburden strata may be split into blocks and tend to topple towards the free face of gully when mining away from the bottom of the gully (upslope direction). The mechanical models showed that, during the period of mining in downslope direction, planar sliding and key fragmental blocks cause a sudden roof shearing off which could result in shock load and, during the period of mining in upslope direction, the overburden blocks may become unstable due to shearing off which could resulted in large shock pressure onto the stope.